Understanding What Clinical Ethical Cases Are: A Review and Perspectives from a Canadian Collaborative Working Group - Saso-Baudaux, Gabriel; Henry, Anna; Gaer, India; Anderson, James; Barned, Claudia; Bell, Jennifer; Buchman, Daniel; de Bie, Lee; Doussau, Adélaïde; Duthie, Katherine; Fortin, Pierrette; Gibson, Jennifer; et al. (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2026)
Clinical ethics is largely about understanding concrete moral situations and supporting meaningful discussion on these to identify appropriate resolutions. However, concepts and methods used to describe cases (e.g., dilemmas, situations, stories) vary between authors and case analysis methods. We undertook a non-exhaustive literature review — inspired by McDougall’s critical interpretive review method — to identify a range of influential ideas on how to describe clinical ethics cases and the methods recommended to understand these cases. We identified nine families of case analysis methods, which vary considerably with respect to the basic description of cases, the strategies recommended to understand cases, and additional features that should be considered (e.g., contexts, social and power dynamics, emotions). As a collective of clinical ethicists and academics, we identify five main limitations of these methods and underline the importance of developing methods based on the practical knowledge of clinical ethics consultants.